Green Organizational Identity: Anticedents And Consequences: An Empirical Study - MUSHTAQUE, TANIA; TUNIO, MUHAMMAD NAWAZ; AKBAR, ZUNERA; JARIKO, MUSHTAQUE (The journal of contemporary issues in business and government, 2021)
Purpose: This study aims to test the framework of green organizational identity to check the positive impact of environmental organizational culture and environmental leadership on green innovation performance and green competitive advantage and via mediator – green organizational identity. Design/methodology/approach: Cross‐sectional research design was applied to this study. Data collected from 400 respondents and proposed hypothesis were verified through Structural Equation Modelling (SEM) technique and mediation analysis. Findings: Findings indicate a positive impact on green organizational identity. Besides this green organizational identity plays a partial mediator role and has a positive impact on green competitive edge and green innovation performance. Small and medium enterprises (SMEs) have a low environmental organizational culture that environmental organizational culture and environmental leadership have significant and environmental leadership than large organizations. SMEs should improve their environmental organizational culture and environmental leadership to enhance the green organizational identity. Practical implications: Through the green organizational identity model organizational will able to enhance their green organizational identity that will give assist to gain green competitive advantage and to improve green innovation performance. Originality/value: This study applies the theory of green organizational identity and develops an integral conceptual model to check its sources and outcomes.